Decline of Peoples Party as Political Force - Shaloom Naeem Gill (International Journal on Orange Technologies, 2021)
Pakistan People‟s party from the day it was formed connected with the masses like no other party in the history of Pakistan. Its socialist slogans and the laborer and peasant friendly policies discussed in their manifesto made Peoples Part a popular party in lower and middle class. People‟s party was a center-left party which had Charismatic leadership. Zulfiqar Ali Bhutto and all his associates were intellectually and politically strong. Moreover Zulfiqar Ali Bhutto was a great orator and he always succeeded in connecting with people through his speeches. After Bhutto was hanged Benazir Bhutto daughter of Zulfiquar Ali Bhutto took charge of party .Benazir also as her father emerged as a charismatic leader as she took her political training from her father. Benazir for two times became Prime Minister of Country and went to self-exile in 1999 and returned to Pakistan in 2007 for the elections of 2008. She was assassinated on 27th Dec 2007 but her party won elections of 2008 and ppp formed its government. Yosuf Raza Gilani became Prime Minister and Asif Ali Zardari became party head and later Head of State of Pakistan. PPP was not able to perform well during its tenure from 2008-2013. Government was alleged of corruption Asif Ali Zardari was a controversial personality and many diehard „jayalas‟ parted their ways from PPP as he was leader. During last days of PPP government opposition raised slogans of “GO ZARDARI GO”. There was security and energy crisis throughout the tenure of PPP .After death of charismatic Benazir There was leadership crisis in the party and government there was no face in Peoples Party with which the masses would be able to connect. In result of all this PPP badly failed in 2013 elections. This research paper is based to find out what were the major reasons which resulted in the worst defeat of PPP. To find this out interviews of important personalities which were associated with PPP will be studied and survey and interviews among the masses of such constituency will be conducted which was stronghold of PPP in 2008 but in 2013 elections PPP faced defeat. This research paper will help us to find out why and how such popular party is facing decline these days. And is its decline momentary like previously it was in Zia-ul-haq‟s and Musharraf‟s era or it will remain with the party for longer period of time